The preparation technology and application of xylo-oligosaccharide as prebiotics in different fields: A review - Huang, Caoxing; Yu, Yuxin; Li, Zheng; Yan, Bowen; Pei, Wenhui; Wu, Hao (Frontiers in Nutrition, 2022)
Xylo-oligosaccharide (XOS) is a class of functional oligosaccharides that has been demonstrated with prebiotic activity over several decades. XOS has several advantages relative to other oligosaccharide molecules, such as promoting root development as a plant regulator, a sugar supplement for people, and prebiotics to promote intestinal motility utilization health. Now, the preparation and extraction process of XOS is gradually mature, which can maximize the extraction and avoid waste. To fully understand the recent preparation and application of XOS in different areas, we summarized the various technologies for obtaining XOS (including acid hydrolysis, enzymatic hydrolysis, hydrothermal pretreatment, and alkaline extraction) and current applications of XOS, including in animal feed, human food additives, and medicine. It is hope this review will serve as an entry point for those looking to prebiotic field of research, and perhaps begin to dedicate their work towards this exciting classification of bio-based molecules.